2021
DOI: 10.1002/cjoc.202000448
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding toward Isonitrile Group Biosynthesis and Mechanism

Abstract: Isonitrile group has been identified in many natural products. Due to the broad reactivity of N≡C triple bond, these natural products have valuable pharmaceutical potentials. This review summarizes the current biosynthetic pathways and the corresponding enzymes that are responsible for isonitrile‐containing natural product generation. Based on the strategies utilized, two fundamentally distinctive approaches are discussed. In addition, recent progress in elucidating isonitrile group formation mechanisms is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 85 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…The reactions were analyzed using liquid chromatography coupled mass spectrometry (LC-MS). These results are consistent with other Fe/2OG isocyanide forming enzymes found in isocyanide-containing lipopeptides , and set the stage to test our hypothesis that AecA and AmcA may utilize an approach similar to the previously identified Fe/2OG enzymes to effect NC triple bond formation. Namely, a conserved process may be employed to forge the isocyanide group by these homologous enzymes in isocyanide-containing lipopeptide and polyketide natural products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were analyzed using liquid chromatography coupled mass spectrometry (LC-MS). These results are consistent with other Fe/2OG isocyanide forming enzymes found in isocyanide-containing lipopeptides , and set the stage to test our hypothesis that AecA and AmcA may utilize an approach similar to the previously identified Fe/2OG enzymes to effect NC triple bond formation. Namely, a conserved process may be employed to forge the isocyanide group by these homologous enzymes in isocyanide-containing lipopeptide and polyketide natural products.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, inspired by a recent discovery that an olefin group can effectively redirect the reactivity of leucine 5-hydroxylase from hydroxylation to epoxidation, the oxidation of 3 may alternatively proceed via oxygen atom transfer (OAT) followed by ring-opening, dehydration, and decarboxylation to afford 4 ( 3 → 7 → 4 , Figure B). Compared with synthetic approaches and other enzymatic approaches used to install isocyanide groups, the Fe/2OG enzyme-catalyzed formation of isocyanide functionalities is unique and may be useful in engineering new synthetic biological approaches for the introduction of isocyanide synthons.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of isonitrile groups by enzymes is unusual, but several have been reported that catalyse the reaction efficiently [37][38][39][40][41][42][43][44]. Most of those enzymes are flavindependent; however, recently, a nonheme iron dioxygenase was identified that biosynthesized an isonitrile group from R-3-((carboxymethyl)amino)butanoic acid through an oxidative decarboxylation reaction [43]. Thus, the isonitrile lipopeptide biosynthesis in Streptomyces coeruleorubidus is performed by a chain of enzymes, whereby the ScoE enzyme performs the oxidative decarboxylation reaction on an iron(II) center in the presence of dioxygen and αKG.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, hundreds of natural products containing isonitrile groups have been discovered and as a consequence, isonitrile-containing compounds have become popular as drug targets. 3,4 Some of these compounds have interesting medicinal properties and act as antifungal, antimalarial and antibacterial entities. [5][6][7] Understanding how nature synthesizes these natural products, therefore, is important.…”
Section: Introductionmentioning
confidence: 99%
“…There are several enzymes in nature responsible for the biosynthesis of isonitrile groups in natural compounds. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] One of those is a nonheme iron enzyme called ScoE, which uses dioxygen and a-ketoglutarate (aKG) as the co-substrate on an iron centre and converts a g-glycine subunit in a peptide chain to isonitrile through initial desaturation followed by decarboxylation. 14 Several crystal structures of ScoE have been reported and the active site structure of the most recent one as reported in the 6XN6 protein databank (pdb) file is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%